End-Stage Renal Disease Patients with Low Serum Albumin: Is Peritoneal Dialysis an Option?. Issue 6 (November 2019) - Singh, Tripti; Astor, Brad C.; Waheed, Sana
Introduction: Low serum albumin is associated with high mortality in patients with end-stage renal disease (ESRD) on chronic dialysis. Clinicians are reluctant to offer peritoneal dialysis (PD) as an option for dialysis for patients with low serum albumin due to concerns of loss of albumin with PD, but evidence supporting differences in outcomes is limited. We evaluated mortality based on dialysis modality in patients with very low serum albumin (< 2.5 g/dL). Methods: We analyzed United States Renal Data System (USRDS) data from 2010 to 2015 to assess mortality by modality adjusted for age, sex, race, employment, number of comorbidities, and year of dialysis initiation. Results: Low serum albumin (< 2.5 g/dL) was present in 78, 625 (19.9%) of 395, 656 patients with ESRD on chronic dialysis. Patients with low serum albumin were less likely to use PD as their first modality than those with higher albumin (3.1% vs 10.9%; p < 0.001). Use of PD was associated with lower mortality compared with hemodialysis (HD) (hazard ratio [HR] = 0.88, 95% confidence interval [CI] 0.81 – 0.95, p < 0.05) in patients with low serum albumin. This difference was more pronounced in patients who had glomerulonephritis (HR = 0.72) or hypertension (HR = 0.81) than in those with end-stage renal disease (ESRD) due to diabetes mellitus or other causes. Conclusion: Peritoneal dialysis is less likely to be the first dialysis modality in patients with low serum albumin requiring dialysis. However, PD is associated with lower mortality than HD in patients with low serum albumin on dialysis. We recommend advocating the use of PD in patients with low serum albumin.